Legal Responsibility of Advocates in Abuse of Power of Attorney from Clients - Kurniawan Kurniawan; Rahmatullah (Indonesian Civil Law Review, 2025)
The legal responsibility of advocates in the context of abuse of power granted by clients is an issue that is increasingly relevant amid the increasing number of deviant legal practices. In particular, this study examines how the actions of advocates who exceed the limits of authority or abuse their power impact the rights of clients and the integrity of the legal profession. The purpose of this study is to analyze the legal basis of advocate liability and identify regulatory weaknesses that cause weak protection for clients. The method used is normative legal research with a statutory and conceptual approach, as well as secondary data in the form of legal literature and court decisions. The results of the study show that there is a regulatory vacuum regarding external supervision, weak code of ethics enforcement, and lack of legal protection for clients. Therefore, it is necessary to carry out regulatory reforms that include the establishment of independent supervisory institutions, revisions of the Advocate Law, and strengthening advocate professional education to be more oriented towards ethics and accountability. This study recommends the need for a legal system that is able to balance the protection of the profession and the rights of the legal services user community.